ANALISIS PERBANDINGAN ECONOMIC VALUE ADDED (EVA) DAN FINANCIAL VALUE ADDED (FVA) SEBAGAI ALAT UKUR PENILAIAN KINERJA KEUANGAN PADA INDUSTRI PERKEBUNAN DI BURSA EFEK INDONESIA - Nora Alverniatha; Samuel Dossugi (Journal of Applied Finance & Accounting, 2010)
Economic Value Added (EVA) and the Financial Value Added (FVA) are the concept of management performance assessment based on the size of the added value which is created by the company during the specified period. EVA measures the economic profit of the company taking into account the cost of capital, whereas FVA earnings measure taking into account the contribution of fixed assets in generating net profits of the company. The study aims to determine the ratio of Economic Value Added (EVA) and the Financial Value Added (FVA) as a measurement of financial performance assessment on the industrial estates listed in Indonesia Stock Exchange for the period 2004 to 2009. The method used a descriptive analysis method using time series data. The results of this study indicated that companies using EVA to create economic value and have a good financial performance from 2004 until 2009. While using the FVA, the company is also able to create a positive financial value of good financial performance from 2004 until 2009. The results also show that there are significantly differences between the EVA and the FVA for the period 2004 to 2009.